Γ–α phase transition of elemental cerium metal. (20th July 2022) - Eryigit, Serpil; Parlak, Cihan; Eryigit, Resul
Abstract: The isostructural γ – α phase transition in elemental cerium has been the subject of many experimental and theoretical studies over almost the past century without a universally agreed upon mechanism. Here, we report the results of an extensive study of electronic and magnetic structures, f -electron number, entanglement entropy, and elastic properties of cerium in the GGA + U framework. We have found that almost all changes in the studied quantities mimic their behavior in the phase transition and could be related to the symmetry of the 4 f occupation and the small change in Hubbard U near a critical value.